Female Self-Initiated Expatriates, Systematic Reviews on Motivations and Challenges - Osman, Zarina; Omar, Rosmini; Nordin, Mohd Norazmi (CENTRAL ASIA AND THE CAUCASUS, 2022)
Expatriation generally more inclined to male talent and less of female becoming expatriate. Overtime expatriation is becoming more popular to female talent. Expatriation has two main types, organization assigned and self-initiated by the individual. It is interesting to understand motivations and challenges being self-initiated expatriate particularly for the female expatriates. The systematic reviews are sought to explain what motivates female to be self-initiated expatriates. Existing research is lacking holistic findings of motivations and challenges experienced by female self- initiated expatriates in the foreign country. The review done on past literatures from three database namely Scopus, Web of Science and Google Scholar focusing on literatures with data related to motivation factors and challenges experienced. Findings show that motivations and challenges experienced by female self-initiated expatriates were different as compared to those female talent being assigned by the company. Based on the review, organization planning to adapt self-initiated expatriate as one of the talent development paths needs to be prepared to support the female talent with specific policy. This systematic literature review contributes to the scarce research on female self-initiated expatriates and acknowledge female self-initiated expatriates as part of member in the community which is male dominated in general.